Examining the Use of Smartphone Apps for Bridging Theory and Practice in Nursing Education: A Systematic Review - Herien, Yelly; Mansur, Arif Rohman; Sari, Ira Mulya; Farlina, Mutia (Basic and Applied Nursing Research Journal, 2024)
The use of smartphone apps or mobile applications has been widely adopted in medical and nursing practices across hospital, health center, and community settings. However, from an academic perspective, par-ticularly in terms of clinical skill proficiency, their use remains limited. This study aimed to systematically synthesize the available literature on smartphone applications and their specific features that can enhance knowledge (theory) and skills (laboratory practice) in undergraduate nursing education. The research findings could serve as the basis for de-veloping the KesPro-P app for laboratory practice in reproductive health nursing at Universitas Andalas. A computerized search was conducted using the ScienceDirect, PubMed, and EBSCOhost databases to identify relevant primary studies published between 2013 and 2023. A total of 10 eligible studies were identified from 431 potentially relevant articles. Six applications were found to be suitable for laboratory practice as they include standard nursing practice procedures. Seven applications were shown to assess changes in students' knowledge, skills, satisfaction, and confidence levels in clinical skills. In almost all of these aspects, smartphone applications scored higher compared to conventional learn-ing methods. By focusing on specific content and incorporating case stud-ies that closely resemble real-world scenarios, the use of smartphone applications proves to be highly effective in helping nursing students de-velop practical and theoretical competencies.